Răspuns :
Răspuns:
Explicație pas cu pas:
E(ₓ)=3(x-2)(x+2)-(x-3)²-9(x-1) +3
E(ₓ)=3*(x²-2²)-(x²-6x+9)-9x+9+3
E(ₓ)= 3x²-12-x²+6x-9x+12 ...............se reduce -12 cu +12
E(ₓ)=2x²-3x-9
E(ₓ)= 2x²-6x+3x-9
E(x) = 2x( x-3)+3(x-3)
E(ₓ)=(x-3)(2x+3) oricare x ∈ R
Explicație pas cu pas:
Explicație pas cu pas:
[tex]\bf E(x) = 3(x - 2)(x + 2) - (x - 3)^2- 9(x - 1) + 3[/tex]
[tex]\bf E(x) = 3 \cdot(x^2 - 2^2) - (x^2 -6x+9)- 9x +9 + 3[/tex]
[tex]\bf E(x) = 3 \cdot(x^2 - 4) -x^2 +6x-9- 9x +12[/tex]
[tex]\bf E(x) = 3x^2 -12 -x^2 -3x +3[/tex]
[tex]\bf E(x) = 2x^2 \green{ \underline{-3x}} -9[/tex]
[tex]\bf E(x) = 2x^2 + \green{ \underline{3x}} -9-\green{ \underline{6x}}[/tex]
[tex]\bf E(x) = 2x^2 +3 \cdot(x -3)-6x[/tex]
[tex]\bf E(x) = 2x \cdot(x-3) +3 \cdot(x -3)[/tex]
[tex] \red{\bf E(x) = (x-3)\cdot (2x+3) ,~\forall ~x\in \mathbb{R}}[/tex]